Spectroscopy of Reperfused Tissue after Stroke Reveals Heightened Metabolism in Patients with Good Clinical Outcomes. Issue 12 (December 2014) - Bivard, Andrew; Krishnamurthy, Venkatesh; Stanwell, Peter; Yassi, Nawaf; Spratt, Neil J; Nilsson, Michael; Levi, Christopher R; Davis, Stephen; Parsons, Mark W
The aim of acute stroke treatment is to reperfuse the penumbra. However, not all posttreatment reperfusion is associated with a good outcome. Recent arterial spin labeling (ASL) studies suggest that patients with hyperperfusion after treatment have a better clinical recovery. This study aimed to determine whether there was a distinctive magnetic resonance spectroscopy (MRS) metabolite profile in hyperperfused tissue after stroke reperfusion therapy. We studied 77 ischemic stroke patients 24 hours after treatment using MRS (single voxel spectroscopy, point resolved spectroscopy, echo time 30 ms), ASL, and diffusion-weighted imaging (DWI). Magnetic resonance spectroscopy voxels were placed in cortical tissue that was penumbral on baseline perfusion imaging but had reperfused at 24 hours (and did not progress to infarction). Additionally, 20 healthy age matched controls underwent MRS. In all, 24 patients had hyperperfusion; 36 had reperfused penumbra without hyperperfusion, and 17 were excluded due to no reperfusion. Hyperperfusion was significantly related to better 3-month clinical outcome compared with patients without hyperperfusion ( P = 0.007). Patients with hyperperfusion showed increased glutamate ( P <0.001), increased N -Acetylaspartate (NAA) ( P = 0.038), and increased lactate ( P <0.002) in reperfused tissue compared with contralateral tissue and healthy controls. Hyperperfused tissue has a characteristic metabolite signature, suggesting that it is more metabolically active and perhaps more capable of later neuroplasticity.